THE USE OF ICT IN AUTHENTIC ASSESSMENT OF THE STUDENTS’ PRODUCTIVE SKILLS - Wardah Zahra; Rita Inderawati; Ismail Petrus (English Review: Journal of English Education, 2019)
Making use of ICT and applying authentic assessment in the teaching and learning activities represent an obligatory from Indonesian Ministry of Education and Culture. This study aimed at finding out types of ICT used in the authentic assessment of the productive skills, describing the implementation of ICT in the authentic assessment of the productive skills, explaining the possible problems faced by the English teachers in the implementation, and explaining the solution used by the teachers to solve the problems. This study was a descriptive study with qualitative approach. The data were collected through interview, observation, and documentation to three English teachers, a curriculum coordinator, a facility and infrastructure administrator, and three students, were validated through methodological triangulations and were analyzed using Miles and Huberman’s analysis model (1994), namely data reduction, data display and conclusion, and verification. The results discovered that there were three types of ICT in the authentic assessment of the productive skills, the teachers had different methods in implementing the three types of ICT tools based on the types of authentic assessment concerning aspects of productive skills, they encountered three main problems in the implementation, and they were educated and motivated to have their solutions to overcome the difficulties.